To graph the function rule y = 6x, we can choose a few values for x and find the corresponding values for y. Let's choose x = -2, -1, 0, 1, and 2.
For x = -2:
y = 6(-2) = -12
So we have the point (-2, -12).
For x = -1:
y = 6(-1) = -6
So we have the point (-1, -6).
For x = 0:
y = 6(0) = 0
So we have the point (0, 0).
For x = 1:
y = 6(1) = 6
So we have the point (1, 6).
For x = 2:
y = 6(2) = 12
So we have the point (2, 12).
Now let's plot these points on a graph and connect them with a line:
(-2, -12)
(-1, -6)
(0, 0)
(1, 6)
(2, 12)
The graph of y = 6x is a straight line that passes through these points.
Begin by replacing x with values in the domain in order to find a few points. Plot these points, then connect the points with a line.
Graph the function rule.
y = 6x
1 answer